Effects of hormonehCG following injection of estnanate of reproductive performances ofswamp buffalo (Bubalus bubalis) - Polmer Situmorang; Abdul Rachman Siregar (Indonesian Center for Animal Research and Development (ICARD), 1998)
Low reproductive performance of buffalo resulted the population growth in Indonesia was only slightly increase during the last 50 year. Reproductive performance can be improved by hormone treatment during synchronization . One study was conducted in Porsea and Siborong-borong to see the effects of hormone hCG on the reproductive performances of swamp buffalo . A total of 34 buffaloes were kept in field grazing and commercial concentrate 4 kg/head/day was given for supplementation in 27 buffaloes and the rest 7 buffaloes treated as control with no supplemeniation . Synchronization performed by two intromuscular (IM) injections of2 ml estrumate in 11 days interval . The buffaloes were divided into 2 groups of 16 buffaloes without hCG (Control group) and 18 buffaloes with hCG (Treated group). Treated group wereinjected with 500 IU hCG intro-muscularly (IM) 24-48 hours following second injection of estrumate . All buffaloes were artificially inseminated (AI) 48 and 72 hours after the second injection of estrumate. Results showed that injection of estrurnate twice in 11 days interval was very effective to synchronize oestrus of buffaloes. The persentage of buffalo showing oestrus was 67 .5 and 85 .3% following 48 and 72 Ins of thesecond injection of estrumate resfectively . The effectiveness of estrumate was significantly affected by body condition of buffaloes where the persentage of oestrus 48 and 72 hours following estrumate injection was significantly higher (P<0.01) in buffaloes with good body condition than those in poor body condition (74.5 and 92.5% vs 42 .9 and 57 .1%). Injection ofhCG following estrumate increased the percentage of oestrus and pregnancy of buffalo. Percentages of oestrus of buffaloes 48 and 72 hours following estrumate injections was significantly higher (P<0 .01) in hCG treatment (83 .3 and 100%) than those in control groups (68 .8 and 81 .3%) . The pregnancy rate of buffalo with good body condition was significantly higher (P<0.01) in group of buffaloes with hCG than those control groups ( 86 .6 vs 50.0%) . It is concluded that injection of hCG following estrumate can improve the reproductive performance ofswamp buffalo Keywords : Swamp buffaloes, hCG, oestrus, body condition